Late health effects of radiation exposure: New statistical, epidemiological, and biological approaches*. (August 2013) - Jacob, Peter; Stram, Daniel O.
Abstract Purpose: The 2012 Conference on Radiation and Health in Kennebunkport, Maine, USA, brought together epidemiologists, statisticians, basic scientists, and clinical scientists interested in the health effects of radiation exposure due to medical, diagnostic, occupational, and non-medical sources, to review the current status of epidemiologic and clinical research on radiation exposure in relation to risk of breast, thyroid cancer, and leukemia, cardiopulmonary events, and other late effects. Topics discussed included synergy between radiation exposure and genetic background; late effects of radiation therapy in childhood cancer survivors and several other medically exposed cohorts; leukemia risk seen in Russian and Chernobyl studies, and leukemia risk from computed tomography scans in childhood. Results and conclusions: This report summarizes the presentations at the meeting and discusses their significance in light of earlier studies and of other ongoing research.